The Application of Deep Learning Approaches in Mathematics Learning: A Literature Review Study - Salma, Emilia; Wijayanti, Dyana (Department of Mathematics Education University of Muhammadiyah Malang, 2025)
Mathematics learning often faces challenges such as monotonous and teacher-centered methods, which can reduce student interest and motivation. The Deep Learning approach offers an innovative alternative by positioning students as active subjects in the learning process. This approach emphasizes in-depth understanding through three main pillars: Mindful Learning, Meaningful Learning, and Joyful Learning. The study employed a Systematic Literature Review (SLR) method by analyzing eight empirical articles published between 2021–2025 related to the implementation of the Deep Learning approach in mathematics learning. The finding indicate that the Deep Learning approach can foster in-depth conceptual understanding. In addition, this approach can also improve the quality of learning by making students the main subjects and actively involved during the learning process. This study is expected to provide a comprehensive overview for educators and researchers in designing adaptive and effective mathematics learning in the 21st-century education era.